Unlocking the potential of Pt-based and metal oxides catalysts in liquid fuel cells technologies: Performance and challenges - Che Ramli Z.A.; Pasupuleti J.; Zainoodin A.M.; Nik Zaiman N.F.H.; Ahmad K.N.; Raduwan N.F.; Yusoff Y.N.; Wan Isahak W.N.R.; Tengku Saharuddin T.S.; Kiong S.T. (Ain Shams University, 2025)
Direct liquid fuel cells (DLFCs) have garnered significant attention due to their ease of utilization and high energy efficiency. Several DLFC technologies have been developed, including Direct Methanol Fuel Cells (DMFCs), Direct Ethanol Fuel Cells (DEFCs), Direct Formic Acid Fuel Cells (DFAFCs), Direct Glycol Fuel Cells (DGFCs), Direct Ethylene Glycol Fuel Cells (DEGFCs), Direct Dimethyl Ether Fuel Cells (DDEFCs), Direct Borohydride Fuel Cells (DBFCs), Direct Alcohol Fuel Cells (DAFCs), and Direct Hydrazine Fuel Cells (DHFCs), as alternative energy sources. This article reviews recent advancements in DLFCs, covering their working principles, the catalysts used for electrocatalytic oxidation, and single-cell performance. A particular focus is placed on the development of platinum (Pt)-based bimetallic, trimetallic, and metal oxide catalysts, which have shown significant potential as anodic electrocatalysts in DLFC technologies due to their enhanced catalytic activity, CO tolerance, and durability. The morphology and structure of these electrocatalysts are characterized using techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM), field-emission scanning electron microscopy (FESEM), and X-ray photoelectron spectroscopy (XPS). Each of these methods offers distinct advantages and limitations in the analysis of fuel cell materials. Additionally, advanced analytical tools like in-situ/operando analysis, and Density Functional Theory (DFT) are increasingly being employed to gain deeper insights into the structure evolution and properties-performance relationship of electrocatalysts during electrochemical processes. This review also discusses the electrochemical properties and parameters that influence DLFC performance. Finally, the challenges in DLFC development are highlighted, and prospects for future advancements in this field are discussed. This review aims to inspire further exploration of these materials in various DLFC technologies and other related fields. ? 2024 The Authors